ANALISA DAYA SAING DAN PENERAPAN STRATEGI DI LINGKUNGAN PENDIDIKAN ISLAM - Nanik Ulfa; Siti Muawanatul Hasanah (RAHMATAN LIL ALAMIN: JOURNAL OF PEACE EDUCATION AND ISLAMIC STUDIES, 2019)
Islamic education institutions as agents of change to pay attention to the demands of improving the quality of madrasah education. For this reason, madrasah leaders need to conduct analysis to map the trends and strengths of competition, set quality standards, and formulate demands for environmental needs and trends. The strategy formulation process includes three stages, namely: the input stage, the matching stage, and the decision stage. In this model, nine matrix techniques will produce one strategy that will be executed in the next strategy management process, namely the implementation of the strategy